Analisis Return Saham yang Dimoderasi Ukuran Perusahaan pada Perusahaan Kesehatan di Bursa Efek Indonesia - Rahmawati, Rizka Yulia; Nur, Dhani Ichsanuddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
Stock returns are the profit earned by investors from owning shares in a company. This study aims to analyze the impact of profitability and leverage on stock returns, This study aims to analyze the effect of profitability and leverage on stock returns, with firm size as a moderating variable, in healthcare companies listed on the Indonesia Stock Exchange from 2020 to 2023. The study population consists of all healthcare companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in 14 companies that met the criteria. Data analysis was conducted using Moderated Regression Analysis (MRA). The results indicate that profitability has a contribution to stock returns, leverage has no contribution to stock returns, firm size moderates the relationship between profitability and stock returns but does not moderate the relationship between leverage and stock returns for healthcare companies listed on the Indonesia Stock Exchange.